Analisis Sentimen Masyarakat Mengenai RUU Perampasan Aset Di Twitter Menggunakan Metode NaÃ¯ve Bayes - kivandi Nugroho; Firman Noor Hasan (LPPM UBHINUS MALANG, 2023)
The development of the world is growing especially in social media, one of which is Twitter. Twitter itself is a social media that can be accessed by various groups to communicate, besides that there are various kinds of public opinions that are quite varied. Data collection from Twitter can be used to conduct sentiment analysis in order to find out public opinion. The research conducted by researchers is an analysis of public sentiment regarding RUU Perampasan Aset that has never been passed. This research starts from data collection, processing, data implementation and evaluation using rapidminer tools. In the data retrieval process, researchers used the keyword